2016
DOI: 10.5944/openpraxis.8.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of Knowledge among Faculty in a Mega Open University

Abstract: Developments in ICTs and knowledge societies have revolutionized the traditional paradigms of education. There is a lot of emphasis on a culture of sharing and collaboration in the education scenario of today though educators have certain inhibitions about sharing of knowledge, ideas and resources. The present study was undertaken to explore the sharing behaviour of the faculty of the National Open University in India. Data was collected through a structured questionnaire on knowledge sharing behaviour and bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 64 publications
1
20
0
1
Order By: Relevance
“…Some institutions adopt a wholly online instruction approach, while others provide a blended learning type, using supportive systems and implementing tools such as Moodle, Blackboard, Atutor, and CanvasLMS among others. Since the mainstream adoption of online distance learning practices and applications at a higher education level, societies are increasingly replacing their traditional educational paradigms (Santosh & Panda, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some institutions adopt a wholly online instruction approach, while others provide a blended learning type, using supportive systems and implementing tools such as Moodle, Blackboard, Atutor, and CanvasLMS among others. Since the mainstream adoption of online distance learning practices and applications at a higher education level, societies are increasingly replacing their traditional educational paradigms (Santosh & Panda, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers 73 argue that academics tend to hoard knowledge from their colleagues, especially when they possess unique, specialized, and important knowledge that does not belong to others. While studying KSB of faculty members of an Indian university 74 argue that opportunism and self-seeking behavior strongly contributes to knowledge hoarding.…”
Section: Knowledgementioning
confidence: 99%
“…The study identifies other important barriers such as organizational culture, lack of time, workload, lack of technology, lack of organizational commitment. However, the barriers to knowledge sharing are usually classified into (i) organizational factors, (ii) technical factors, and (iii) individual factors 6,7,8,9,10,11,12 . For instance 13 , conducts a comprehensive review of general barriers to KS and identifies three dozen barriers under these three categories: (i) organizational barriers such as lack of transparent rewards and recognition and supportive organizational culture, (ii) individual barriers such as fear of lack of time, jeopardizing job security, and lack of trust, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, e-learning is not growing as fast as the e-commerce sector in the country. One reason for this could be the traditional cultural mindset of the population which prefers individual and book/lecture-based learning, and also their lack of faith in network-based knowledge sharing (Santosh & Panda, 2016).…”
Section: Ict and Distance Educationmentioning
confidence: 99%
“…In a study on the National Open University, Panda and Mishra (2007) reported significant barriers to e-learning as perceived by faculty, namely: access to technology and training on e-learning, institutional policy, and instructional design for e-learning. Santosh and Panda (2016) reported faculty preference for colleagues and publishing, rather than sharing in social and professional networks (and the absence of organizational recognition and incentives). This is notwithstanding the fact that a study of learner preferences suggested a preference for web-based learning, supported by print and some form of online and/or faceto-face interaction; and such an offering could be further facilitated by email and interactive multimedia support (Dikshit, Gaba, Bhushan, Garg, & Panda, 2003).…”
Section: Issues Concerns and The Futurementioning
confidence: 99%